2017
DOI: 10.1002/jso.24688
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy in resectable synovial sarcoma

Abstract: In this national cohort, AC was associated with prolonged OS for SS for stage III patients but not in lower stages. Less restricted use of this therapy may be warranted in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…The role of adjuvant therapy in SS is highly debated. Two large registry‐based studies showed a clinical benefit of adjuvant chemotherapy in patients with stage III SS . Contrarily, a pooled analysis of two European Organisation for Research and Treatment of Cancer (EORTC) phase III clinical trials found no correlation between adjuvant chemotherapy and better overall survival (OS) in SS patients .…”
Section: Discussionmentioning
confidence: 99%
“…The role of adjuvant therapy in SS is highly debated. Two large registry‐based studies showed a clinical benefit of adjuvant chemotherapy in patients with stage III SS . Contrarily, a pooled analysis of two European Organisation for Research and Treatment of Cancer (EORTC) phase III clinical trials found no correlation between adjuvant chemotherapy and better overall survival (OS) in SS patients .…”
Section: Discussionmentioning
confidence: 99%
“…As far as resectable, non-metastatic synovial sarcomas in the extremities are concerned, it has been reported that neoadjuvant chemotherapy (mesna/adriamycin/ifosfamide/dacarbazine) decreases distant metastasis and improves survival time, 13 while adjuvant chemotherapy has been reported to lead to a slight but definite risk reduction in local recurrence, distant recurrence, and overall recurrence. 14 From another study, 15 it seems that locally aggressive tumors benefit more from chemotherapy than those which are not. However, despite these positive reports, the long-term benefit of chemotherapy on survival is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Chen et al (16) reported that adjuvant chemotherapy improved disease-specific survival and prolonged the time to metastasis in stage IIB/III SS patients. Recently, Vining et al (17) reported improved outcomes with adjuvant chemotherapy in stage III SS patients from an analysis of the National Cancer Database and recommended less restricted use of adjuvant chemotherapy for stage III SS. These differences might come from varying use of chemotherapy regimens among patients and different proportions of N/AC administration.…”
Section: Discussionmentioning
confidence: 99%